2019
DOI: 10.1002/ecs2.2699
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐predator mechanisms in evolutionarily predator‐naïve vs. adapted fish larvae

Abstract: It is a fundamental feature of evolution that natural selection acts on individuals to adapt to predation pressure via the development of anti‐predator mechanisms. As such mechanisms are costly in terms of energy and time, species living in habitats where predators are rare or absent were expected to show reduced predator responses. Such a reduction was expected for larvae of the native whitefish (Coregonus wartmanni) in Upper Lake Constance, as these pass their initial stage in a historically predator‐free pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 54 publications
2
22
0
Order By: Relevance
“…The massive recent increase in stickleback abundance coincides with a sharp decline in pelagic whitefish (Coregonus wartmanni, Bloch, 1784) yields, both in the number of individuals caught, and their weight-at-age (Rösch et al, 2017). Previous work has speculated that the invasive stickleback population could have a negative impact on whitefish growth and abundance, and shows that stickleback will prey on whitefish larvae in laboratory foraging experiments (Roch et al, 2018;Ros et al, 2019) or following stocking (Roch et al, 2018). However, the first stickleback population expansion during the eutrophication period in Constance coincides with population size increase in whitefish (Numann, 1972), so the relationship between whitefish and stickleback abundances is either mediated by some other factors in the environment, or it is not causal.…”
Section: Examining the Lake Constance Stickleback Population From A Gmentioning
confidence: 99%
See 1 more Smart Citation
“…The massive recent increase in stickleback abundance coincides with a sharp decline in pelagic whitefish (Coregonus wartmanni, Bloch, 1784) yields, both in the number of individuals caught, and their weight-at-age (Rösch et al, 2017). Previous work has speculated that the invasive stickleback population could have a negative impact on whitefish growth and abundance, and shows that stickleback will prey on whitefish larvae in laboratory foraging experiments (Roch et al, 2018;Ros et al, 2019) or following stocking (Roch et al, 2018). However, the first stickleback population expansion during the eutrophication period in Constance coincides with population size increase in whitefish (Numann, 1972), so the relationship between whitefish and stickleback abundances is either mediated by some other factors in the environment, or it is not causal.…”
Section: Examining the Lake Constance Stickleback Population From A Gmentioning
confidence: 99%
“…However, the first stickleback population expansion during the eutrophication period in Constance coincides with population size increase in whitefish (Numann, 1972), so the relationship between whitefish and stickleback abundances is either mediated by some other factors in the environment, or it is not causal. It has been proposed that either competition for pelagic zooplankton resources such as Daphnia -that have declined in abundance with the re-oligotrophication of Lake Constance (Straile and Geller, 1998;Stich and Brinker, 2010;Rösch et al, 2017) -or direct predation on whitefish eggs and larvae (Roch et al, 2018;Ros et al, 2019) are responsible for this reduction in yield. Predation by sticklebacks on eggs and juveniles of their own species occurs frequently (Whoriskey and FitzGerald, 1985;Hyatt and Ringler, 1989;Smith and Reay, 1991;Foster and Bell, 1994;Manica, 2002;Mehlis et al, 2010) along with predation on larvae of other fish species (Hynes, 1950;Manzer, 1976;Delbeek and Williams, 1988;Kean-Howie et al, 1988;Gotceitas and Brown, 1993;Nilsson, 2006;Kotterba et al, 2014;Byström et al, 2015), while previous studies on stickleback populations in the Baltic Sea have suggested that intraguild predation on eggs and juvenile fish is responsible for the observed declines in perch (Perca fluviatilis, Linnaeus, 1758) and pike (Esox lucius, Linnaeus, 1758) recruitment (Nilsson, 2006;Bergström et al, 2015;Byström et al, 2015;Nilsson et al, 2019;Eklöf et al, 2020).…”
Section: Examining the Lake Constance Stickleback Population From A Gmentioning
confidence: 99%
“…As an opportunistic species, the ability of sticklebacks to adapt to different and multiple food sources plays a significant role across the different life stages [ 31 ]. It was recently shown that the success of stickleback predation on fish larvae depends upon the size and species of prey [ 32 , 33 ]. Quantitative examination of predation on roach ( Rutilus rutilus ), perch ( Perca fluviatilis ) and whitefish ( Coregonus wartmannii ) larvae shows a particularly high toll on small-sized whitefish larvae which historically grew up in habitat without predators, in comparison to similar-sized larvae of the other two species which have co-evolved with predators in their environment [ 32 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sticklebacks have recently increased strongly in abundance in the pelagial of Lake Constance prompting concern that predation on whitefish larvae may be of ecological importance [ 34 ]. Stickleback hunting success has been shown to decrease with prey size and with increasing variation in predator avoidance strategies shown by prey [ 33 ], but it has not been analysed thus far whether these differences might be related to larval swimming performance as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation